Absolute quantification of viruses by TaqMan real-time RT-PCR in grapevines - Fajardo,Thor Vinícius Martins (2017)
ABSTRACT: The absolute quantification determines the absolute amount of a targeted nucleic acid expressed as a copy number or concentration. The knowledge of virus concentrations in commercial crops possesses high relevance to ensure a reliable diagnosis. The objective of this study was to perform an absolute quantification of five viruses in infected grapevines (Vitis spp.). Different known amounts of the standard sample (cloned viral cDNA or in vitro transcribed viral RNA) were quantified by TaqMan RT-qPCR. Based on these data, standard curves were generated plotting Ct values (threshold cycle) against the log of the standard sample amount. Infected grapevine samples were evaluated to determine virus titers, which were highly variable. This result may contribute to improve virus diagnosis by accurately quantifying virus titre variations in grapevines.